Perspectives for using classical neural network models and methods of counteracting attacks on network resources of information systems - Aitchanov, B.; Korchenko, A.; Tereykovskiy, I.; Bapiyev, I. (My University, 2017)
The article is devoted to the development of the methodological base for increasing the efficiency of using neural network models for the recognition of cyber-attacks on the network resources of information systems. It is shown that the efficiency of use largely depends on the type of neural network model. The list of the main conditions of the recognition problem is determined, which should be provided due to the characteristics of the type of the neural network model. A number of parameters have been developed, the values of which make it possible to determine the degree of such security. As a result of studies of the main types of classical neural network models, the values of these parameters were determined for each of them. Using the parameters obtained and taking into account the expected application conditions, the perspectives of using the main types of classical neural network models are estimated for the recognition of cyber-attacks. The ways of development of neural network systems for the recognition of cyber attacks on network resources are considered. It is shown that a promising way of such development is the rulemaking for determining effective types of neural network models.Статья посвящена разработке методологической базы повышения эффективности использования нейросетевых моделей для распознавания кибератак на сетевые ресурсы информационных систем. Показано, что эффективность использования во многом зависит от типа модели нейронной сети. Определен перечень основных условий задачи распознавания, которые должны быть обеспечены с учетом особенностей типа модели нейронной сети. Разработан ряд параметров, значения которых позволяют определить степень такой безопасности. В результате исследований основных типов классических моделей нейронных сетей были определены значения этих параметров для каждой из них. По полученным параметрам и с учетом ожидаемых условий применения оцениваются перспективы использования основных типов классических моделей нейронных сетей для распознавания кибератак. Рассмотрены пути развития нейросетевых систем для распознавания кибератак на сетевые ресурсы. Показано, что перспективным путем такого развития является нормотворчество для определения эффективных типов моделей нейронных сетей.
News of the National Academy of Sciences of the Republic of Kazakhstan, Series of Geology and Technical Sciences.
Keywords: импакт-фактор 2017; скопус; зарубежные авторы; научный журнал; отечественное издание; процентиль 26 (2019); кибератака; информационные системы